The Dark Side Of Artificial Intelligence-Based Personalization: Intrusiveness, Trust, And Consumer Resistance On E-Commerce Platforms - Bonitian Rifiansyah; Yudi Nur Supriadi; Alfatih Sikki Manggabarani (UNIVERSITAS PAKUAN, 2026)
The development of Artificial Intelligence (AI) has encouraged companies to implement personalization strategies in digital marketing through e-commerce platforms and social media. Although AI-based personalization can improve consumer experience and marketing effectiveness, overly intensive personalization may also generate negative responses in the form of consumer resistance. This study aims to analyze the effect of AI personalization on consumer resistance by considering the mediating roles of perceived intrusiveness and customer trust. This study employed a quantitative approach using an explanatory research method. Data were obtained by distributing online questionnaires to 400 active users of digital platforms in Indonesia and were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that AI personalization affects perceived intrusiveness, customer trust, and consumer resistance. Perceived intrusiveness is proven to increase resistance behavior, whereas customer trust reduces resistance behavior. In addition, perceived intrusiveness and customer trust are able to mediate the relationship between AI personalization and consumer resistance, both partially and sequentially. This study shows that overly intensive AI personalization can generate intrusive perceptions, reduce consumer trust, and increase resistance to digital marketing. These findings contribute to the development of the literature on the dark side of AI-based personalization and provide input for companies in designing personalization strategies that are more balanced and oriented toward consumer comfort.